ESR investigation of NR and IR rubber vulcanized with different cross-linking agents - P. Posadas (2018)
© BME-PT. This study evaluates the formation of radical species in natural rubber (NR) and poly-isoprene rubber (IR) during the vulcanization process and the uniaxial deformation of the formed networks by means of Electron Spin Resonance (ESR). Vulcanization of NR and IR always shows a radical pathway, where the different vulcanization systems dictate the concentration of radical species in the course of this complex process. The greatest concentration of radicals were detected during the vulcanization with sulfur/accelerator based on efficient systems (EV), followed by conventional (CV) and sulfur donor systems, whereas azide and organic peroxide agents showed smaller concentration of radicals. Independently of the vulcanization system, certain amount of radicals was detected on the vulcanized samples after the end of the vulcanization process. Comparison between different matrices demonstrates that NR always shows higher concentration of radicals than IR in the vulcanization process as well as during uniaxial deformation, fact that could be associated to the presence of nonrubber components in NR.